2015
DOI: 10.1152/ajpcell.00383.2014
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase A stimulates Kv7.1 surface expression by regulating Nedd4-2-dependent endocytic trafficking

Abstract: The potassium channel Kv7.1 plays critical physiological roles in both heart and epithelial tissues. In heart, Kv7.1 and the accessory subunit KCNE1 forms the slowly activating delayed-rectifier potassium current current, which is enhanced by protein kinase A (PKA)-mediated phosphorylation. The observed current increase requires both phosphorylation of Kv7.1 and the presence of KCNE1. However, PKA also stimulates Kv7.1 currents in epithelial tissues, such as colon, where the channel does not coassemble with KC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
1
8
1
Order By: Relevance
“…Indeed, beat frequency-corrected FPDs were essentially invariant in stressed KCNQ1 -expressing cells compared to unstressed ones, which highlights the robustness of this adaptation system. Finally, our data are not at odds with previously published K v 7.1 trafficking mechanisms, notably RAB11-based slow recycling, as these may well play a role in ensuring homeostatic I Ks levels in cardiomyocytes or other contexts (Seebohm et al, 2007 ; Andersen et al, 2015 ). Likewise, our results are not redundant with those by Wang et al ( 2013 ) who proposed endoplasmic reticulum fragmentation as a slow-rate K v 7.1 trafficking mechanism.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Indeed, beat frequency-corrected FPDs were essentially invariant in stressed KCNQ1 -expressing cells compared to unstressed ones, which highlights the robustness of this adaptation system. Finally, our data are not at odds with previously published K v 7.1 trafficking mechanisms, notably RAB11-based slow recycling, as these may well play a role in ensuring homeostatic I Ks levels in cardiomyocytes or other contexts (Seebohm et al, 2007 ; Andersen et al, 2015 ). Likewise, our results are not redundant with those by Wang et al ( 2013 ) who proposed endoplasmic reticulum fragmentation as a slow-rate K v 7.1 trafficking mechanism.…”
Section: Discussioncontrasting
confidence: 55%
“…RAB GTPases are key mediators of intracellular trafficking and have previously been associated with K v 7.1 recycling, albeit so far with mediating slow-rate ion channel turnover in non-cardiac cell contexts (Seebohm et al, 2007 ; Balse et al, 2012 ; Abbott, 2014 ; Andersen et al, 2015 ). hiPSC-CMs appeared to be refractory to the transfection of DNA constructs but we found that in-vitro transcribed mRNA could efficiently be delivered into these cells (Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C-terminus of KCNQ1 has been shown to interact with the C-terminus of KCNE1, and form a macromolecular complex with other molecules, including PI(4,5)P2, calmodulin, Nedd4.2 and AKAP-Yotiao, responsible for proper assembly, function and regulation of the channel [47][48][49][50][51]. KCNE1 expression has been shown to be important for regulation of the channel by PKA, PI(4,5)P2 and acute activation of the channel by PKC [6,7,13].…”
Section: Discussionmentioning
confidence: 99%
“…MDCK cells constitute an excellent cell system for studying trafficking of membrane proteins, such as ion channels [ 13-18 ]. The MDCK cells are, when grown to confluency, polarized cells with an apical and a basolateral membrane.…”
Section: Introductionmentioning
confidence: 99%